Investigation of powdery & downy mildew segregation in Bogazkere hybrids of Turkish wine grape - Metehan Gunhan; Angelica Jermakow; Nayana Arunasiri; Ian Dry (OENO One, 2023)
Powdery mildew (Erysiphe necator syn. Uncinula necator) and downy mildew (Plasmapora viticola) are the most harmful diseases to grapevine production in Turkey. The aim of this study was to generate hybrids between the susceptible Turkish wine grape variety ‘Bogazkere’ and powdery and downy mildew resistant microvine breeding lines and evaluate their resistance to these important diseases. Marker Assisted Selection (MAS) was used to determine the inheritance of powdery and downy mildew resistance and flower sex loci of the 36 F1 progeny plants obtained by cross-pollination at genotypic level. Based on the PCR results, phenotyping and leaf bioassay were performed to validate initial MAS for 11 and 9 representative progeny with four resistant and susceptible controls. As a result, two tall powdery and downy mildew-resistant vines, three powdery mildew-resistant microvines and two downy mildew-resistant microvines were obtained. The MAS results were also validated by leaf bioassays, which confirmed that resistance genes segregated to the F1 progeny are functional and provide resistance. To the best of our knowledge, this research provides the first photographic validation of the powdery and downy mildew resistance of the Turkish variety ‘Bogazkere’. Our findings could potentially provide the wine industry with a resistant wine grape cultivar and an addition to the wine grape germplasm, which could contribute to future breeding programs. Most importantly, the success of the resistance genes segregated into the candidate progeny could help significantly reduce the use of chemicals against grapevine pathogens.